Pachyneuridae (Diptera): new data on the geographic range and designation of the lectotype of Pachyneura fasciata Zetterstedt, 1838 - Paramonov, Nikolai M.; Salmela, Jukka (Zootaxa, 2016)
All available records of two nematoceran flies Pachyneura fasciata and P. oculata were gathered and mapped. P. fasciata is a wide-ranging Palaearctic species, and is here reported for the first time for some regions of the Russian Federation, including the European part of Russia (Leningrad Oblast), Western Siberia (Tomsk Oblast, Altay Republic), Eastern Siberia (Krasnoyarsk Krai, Irkutsk Oblast, Chita Oblast), the Far East of Russia (Kuril islands, Kunashir and Paramushir Islands), and for continental China. Pachyneura oculata has a restricted eastern Palaearctic range. The lectotype of P. fasciata has been designated and a key for the identification of Pachyneura species is provided.